Ways to improve the gene pool of pigs of the Russian Federation - V. A. Bekenеv (Вавиловский журнал генетики и селекции)
An analysis of the system of breeding work in the pig industry of our country has been carried out. The scientifc and organizational factors that determine the improvement of breed and productive qualities of pigs have been analyzed. On the basis of many years of experimental data, selection practices obtained in the process of creating new breeding achievements, and using the scientifc results of the world science on genetics and animal breeding, proposals have been developed for a new system for assessing and improving the genetic potential of animal productivity based on modern achievements in genetics. In particular, a critical analysis was performed on the existing instructions for boning pigs, linear breeding, which does not meet the criteria of reality in the systematization of biological objects. The positive eﬀect of breeding pigs in a closed mode in the form of a “line-population”, using such genetic markers as erythrocyte antigens, erythrocyte enzymes, lipoproteins, allowing intensifcation of the selection process, has been experimentally proved. When hogging pigs and developing breeding plans with a herd, it was proposed to use such selection and genetic parameters as heritability factors, phenotypic and genetic correlations, selective diﬀerential, selective eﬀect, etc. for assessment of animals and prognostication of productivity. A system of continuous scoring of each selectable feature was developed, in contrast to the interval to the classes used in our country at the present time. A model of the selection index, taking into account the selection and economic signifcance of each of its components, has been proposed. Theoretical paths have been shown towards and experimental proof given to a relatively rapid transformation of breeds of animals bred in Russia to world-class productivity, as opposed to the constant import of breeding animals.